Treatment concept of chronic subdural haematoma according to an algorithm using evidence-based medicine-derived key factors: a prospective controlled study - Weigel, Ralf; Schlickum, Linda; Weisser, Gerald; Krauss, Joachim K. (British journal of neurosurgery, 2015)
Introduction. Surgical treatment for chronic subdural haematoma (CSH) has been analysed by applying evidence-based medicine (EBM) criteria earlier. Whether implementation of EBM-derived key factors into an optimised treatment algorithm would improve outcome, however, needs to be clarified.Material and methods. Symptomatic patients with CSH who fulfilled the inclusion criteria were either assigned to an optimised treatment algorithm (OA-EBM group) or to a control group treated by the standard departmental surgical technique (SDST group) in a prospective design. For the OA-EBM algorithm only one burr hole, extensive intraoperative irrigation and a closed system drainage with meticulous avoidance of entry of air was mandatory. A two-catheter technique was used to reduce intracavital air. Final endpoints were neurological outcome (Markwalder Score), recurrence and the amount of intracranial air.Results. A total of 93 out of 117 patients were evaluated accounting for 113 cases because 20 patients had bilateral haematomas. Demographic data of 68 cases in the SDST group did not differ from 45 cases in the OA-EBM group. The Markwalder Score showed greater improvement in the OA-EBM group (0.5 ± 0.6 vs. 1.0 ± 1.0, p = 0.003). The recurrence rate was 18% (12 patients) in the SDST group versus 2% (1 patient) in the OA-EBM group (p < 0.05). The amount of intracranial air was significantly lower in the OA-EBM group (3.3 ± 5.0 cm3vs. 5.2 ± 7.7 cm3) with p = 0.04. In the standard group computerised tomography scanning was performed slightly earlier (3 ± 1.7 days vs. 3.6 ± 1.4 days). When comparing only non-recurrent cases in both groups no significant difference was apparent.Conclusions. Implementation of EBM key factors into a treatment algorithm for CSH can improve neurological outcome in a typical neurosurgical department, reduce recurrence and minimise the amount of postoperative air within the haematoma cavity.